The impact of dynamic locking on collaborative programming - Shatte, Adrian; Holdsworth, Jason; Lee, Ickjai (ACIS, 2014)
The parallel strategy of collaborative writing is commonly used by academia and industry. However, the nature of this approach may not scale to other genres of collaboration including collaborative programming. In this paper, we present a web-based prototype that supports parallel programming with the use of dynamic locking, and evaluate its scalability and system usability. Our results suggest there are benefits to our approach, and we discuss the implications and future directions for research.